ANALISIS PEMASARAN RUMPUT LAUT DI DESA AKUNI KECAMATAN TINANGGEA KABUPATEN KONAWE SELATAN - Siti Kadri Yanti Sari; Waode Harliyanti Unga; Citra Ayu Ningsi; Asis Bujang (Journal Publicuho, 2024)
This research aimed to analyze seaweed marketing in Akuni Village, Tinanggea Sub-district, Konawe Selatan Regency. The study was motivated by the large potential of seaweed in Indonesia, particularly in Akuni Village, where seaweed cultivation is the main livelihood for most residents. The research method used was a survey method with a qualitative descriptive approach. Data were collected through interviews, observation, and documentation. Data analysis was carried out using qualitative descriptive analysis to describe marketing channels and quantitative descriptive analysis to calculate marketing margins and marketing efficiency using marketing margin and farmer's share formulas. The results showed that there was one seaweed marketing channel in Akuni Village, namely from farmers to collectors, then to Makassar. The marketing margin obtained by collectors is Rp. 3,000/Kg. Marketing efficiency is relatively high with a farmer's share value of 83%. In conclusion, the seaweed marketing channel in Akuni Village is quite good and efficient.